Evaluasi Kinerja Progam Keluarga Harapan (PKH) Dalam Meningkatkan Kesejahteraan Masyarakat Miskin Di Kecamatan Tanjungpinang Barat Kota Tanjungpinang - Erva Afriyana; Dedek Hardiyanti; Dian Putri Sartika (CV. ITTC INDONESIA, 2025)
The Family Hope Program (PKH) in West Tanjungpinang District aims to improve the welfare of the community, particularly poor families, through cash assistance. This study evaluates PKH's performance within the context of the complexity of poverty in Indonesia and government efforts to address it. Although program outputs have met targets, gaps in aid distribution and a lack of public understanding of the program remain. Accurate data validation and intensive mentoring are crucial to ensure targeted assistance. Challenges encountered include data inaccuracy, lack of public awareness, administrative issues, and potential misuse. The analysis of PKH inputs, processes, outputs, and outcomes highlights the need for ongoing monitoring and evaluation. While the program has potential, improvements in human resources and data management are essential for optimal success. Collaborative efforts between the government and the community are also needed to address existing challenges and ensure the effectiveness of PKH assistance.